One new genus and three new species of deep-sea nematodes (Nematoda: Microlaimidae) from the Southwest Pacific Ocean and Ross Sea - Leduc, Daniel (Zootaxa, 2016)
New deep-sea nematodes of the family Microlaimidae are described from the Southwest Pacific Ocean and Ross Sea. Microlaimus korari n. sp. is characterised by annulated cuticle with longitudinal bars, round amphideal aperture slightly smaller than the cryptospiral amphideal fovea, spacious and heavily cuticularised buccal cavity with large dorsal tooth and right subventral tooth situated anteriorly relative to left subventral tooth, slender spicules 4.4 cloacal body diameters long, and gubernaculum 1.2 cloacal body diameters long with laterally curved distal end and swollen proximal end. Bolbolaimus tongaensis n. sp. is characterised by annulated cuticle with longitudinal bars, oval amphideal aperture and cryptocircular amphideal fovea situated between cephalic setae and only partially surrounded by cuticle annulations, and short spicules cuticularised along dorsal edge and at proximal end and with swollen portion near proximal end. Maragnopsia n. gen. is characterised by a minute, non-cuticularised mouth cavity without teeth, an elongated posterior pharyngeal bulb more than twice as long as it is wide, a single outstretched testis, and a conico-cylindrical tail 13–16 anal body diameters long. A list of all 83 valid Microlaimus species is provided. The present study provides the first microlaimid species records from deep-sea habitats (> 200 m depth) in the Southwest Pacific and Ross Sea. The presence of M. korari n. sp. on both the continental slope of New Zealand and Ross Sea abyssal plain suggests that this species has a wide geographical and depth distribution. However, molecular analyses will be required to confirm the identity of these two geographically disparate populations.